KEPATUHAN PENDERITA TUBERKULOSIS MINUM OBAT ANTI TUBERKULOSIS SECARA MANDIRI - Nixson Manurung; Deddy Sepadha Putra Sagala (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Health is a state of well-being, physically, mentally, spiritually and socially that enables everyone to live a socially and economically productive life. Pulmonary tuberculosis is a global health problem that can impact productivity and quality of life. According to WHO, there are an estimated 1,020,000 new TB cases per year (399 per 100,000 population) with 100,000 deaths per year (41 per 100,000 population). Compliance of pulmonary tuberculosis patients in taking medication is key to the success of tuberculosis treatment. This study aimed to explore patients' perceptions of pulmonary tuberculosis and medication adherence. This study is a qualitative study with a phenomenological approach. Data were collected using in-depth interviews and then analyzed by content analysis. The informants in this study consisted of eight tuberculosis patients. The results of this study found three themes, namely (1) understanding of tuberculosis disease, (2) the impact of tuberculosis disease, (3) patients' perceptions of tuberculosis disease. It was concluded that a better understanding of tuberculosis disease and treatment adherence can contribute to treatment success. It is suggested that patients can be aware and encouraged to take medication regularly.